Avaliação de desempenho da diretoria de desenvolvimento de pessoal em uma instituição pública de ensino superior por meio da metodologia multicritério de apoio à decisão - construtivista - Dagostin, Henrique (2016)
The human resource management department has been not to act in a purely bureaucratic way anymore, and then it is considered as a strategic unit in organizations. Therefore, there is a growing need for studies related to action management on the human resources, what should propose new theoretical debates, models and approaches to the management practices. In this sense, the present work points out to develop a performance evaluation model to support the department of development of people of the Universidade Federal da Fronteira Sul - UFFS, through Methodology Multiple-criteria Decision Analysis – Constructivist. This case study, exploratory and descriptive, was developed with the help of a couple intervention tools, the ProKnow-C, through it was held: (i) the selection of relevant scientific papers on the subject under study; (ii) the bibliometric analysis, being extracted the most relevant articles; authors; journals and keywords on the topic; and, (iii) the systemic analysis of the articles allows to build knowledge in Researcher and identify gaps in the literature of the performance evaluation focused on the development of people in public educational institutions. Using the second policy instrument, the MCDA-C, it was possible to build the organizational performance assessment model, through direct interaction with the decision maker what makes possible describe the objectives; goals; the desirable and the undesirable aspects; problems and concerns on this issue in relation to the context of this inquire; organizing them into a structure that enabled perform the measurement, overall assessment of the current situation and propose improvement actions. The main results of the systemic analysis were: (i) no work identifies the decision-maker at work and take into account for the full construction of the model; (ii) less than 4% of the work recognize that the model is valid only for context in analysis; (iii) all the articles don’t meet the theory of measurement; (iv) only 3 of 29 analyzed articles realize the integration of the criteria for an overall assessment of performance; (v) no work shows improvement actions. The main results of the construction of performance evaluation model were: (i) building of 75 performance indicators; (ii) allowed to obtain the overall performance evaluation, making it possible to visualize weaknesses and strengths of management performance, which is currently 55 points; (iii) allows one to view the impact of actions on the overall performance; and, (iv) made it possible to list 13 actions to promote improvement, so that overall performance leaped from 55 to 79 points. Thus, the study is extremely important for the management of human resources of the UFFS, since: (i) supplies the difficulty of stating that certain result is due to a practice of resource management; (ii) supplies the difficulty of the organization in defining organizational indicators of human resource management that are comparable, before and after interventions; and, (iii) fills a gap in the literature of the studies that consider the uniqueness of the context, taking the decision maker into account for the full construction of the model.